Women's International League for Peace and Freedom At Courthouse Transit Stop Protesting Removal From Buses Their "Think Before You Register For The Draft" Signs - Watkins, Howard::::::::: (1982)
News media recording protesters carrying banned posters onto City bus going north on Fresno Street from Courthouse Park Bus electronic sign says, "32 N FRESNO ST"